Band Structure of an Omnidirectional 1D Dielectric Gratings - J. Prawiharjo; A.A. Iskandar; M.O. Tjia (Institut Teknologi Bandung, 2003)
The one-dimensional Photonic crystal has become an attractive subject of study in view of the recent experimental discovery of its omnidirectional reflectance implying the existence of complete photonic band gaps, which was believed to be possessed only by three-dimensional photonic crystals. This unexpected property has recently been explained numerically. In the present paper, the origin of such property is described and an approximate analytical expression is derived for the band edges of the photonic band gap. The results for some specific structures and materials are demonstrated, showing structures with 0.094% maximum error of the approximated result compared to the complete numerical result.